2014
DOI: 10.1111/ijcs.12108
|View full text |Cite
|
Sign up to set email alerts
|

‘Teaching Young Consumers’ – food safety in home and consumer studies from a teacher's perspective

Abstract: In Swedish compulsory school, the subject home and consumer studies (HCS) is an opportunity to create conscious consumers for the future. In Sweden, it has been estimated that half a million cases of foodborne infections occur each year, which has an impact on public health. The numbers of foodborne infections are affected by actions connected to the four Cs in food safety: cooking, cleaning, chilling and cross‐contamination. As foodborne infections in many cases are suspected to occur in private households, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…A relatively high proportion of food items were stored at higher temperatures than recommended, which indicates that information to consumers should focus on cold food storage. Teachers in home and consumer reported in a previous internet-based questionnaire that their food safety-teaching more often focused on cleaning issues than on issues connected with chilling (Lange et al, 2014). In the present study, the teachers reported that the observational investigation increased interest and knowledge of date labeling, food hygiene, refrigerator storage and food wastage among young students.…”
Section: Cold Food Storagementioning
confidence: 52%
“…A relatively high proportion of food items were stored at higher temperatures than recommended, which indicates that information to consumers should focus on cold food storage. Teachers in home and consumer reported in a previous internet-based questionnaire that their food safety-teaching more often focused on cleaning issues than on issues connected with chilling (Lange et al, 2014). In the present study, the teachers reported that the observational investigation increased interest and knowledge of date labeling, food hygiene, refrigerator storage and food wastage among young students.…”
Section: Cold Food Storagementioning
confidence: 52%
“…With the intention of obtaining an overview of the representation of food safety elements inside formal education, educational objectives were analyzed to obtain insight into the lesson content on the macro level (level of syllabus planner). As reported by Lange and others (), the syllabus was used by 82% of the teachers as a starting point for lesson planning, but also reported as a framing factor (Lange and others ).…”
Section: Discussionmentioning
confidence: 76%
“…The importance of temperature is often addressed. However, gaps in home economics teachers’ food safety knowledge and in their food safety behavior are reported by Lange and others (): 1 out of 5 home economics teachers reported that they did not include the refrigerator temperature in their teaching at all, and another 30% only taught it in theory.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Unusan [31] suggested media campaigns. Lange et al [39] studied teachers' perceptions of food safety at home, and most of the teachers said that schools have the mission to provide knowledge on food safety at home. When evaluating the basic skills at schools, the most performed skills were hand washing, washing up dishes, cleaning of work surfaces, and handling of dishcloths.…”
Section: Discussionmentioning
confidence: 99%